Application of Indian Copyright Act 1957 in Bengali Publication in India: The Application and Impact of the Indian Copyright Act on Bengali Publication Rights and Creators in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian copyright Act consists of 15 chapters and 79 sections. All these sections are not related to publication rights and rights to creators. Section 33 to 43 in Chapters 7, 8, 9 is related to copyright society, Rights of Broadcasting Organization and of Performers, International Copyright. Respectively section 63 to 79 in chapters 13, 14, 15 is related to Offences, Appeals, and Miscellaneous. This paper tries to focus on sections which are related to publication rights and rights to creators. This paper also tries to collect some information from Bengali writers and publishers about application copyright in Bengali publication. The paper shows what is the present scenario of application of copyright in Bengali publication and problems. This paper also reflects scenario of Bengali publication in India previous ten years.